(untitled) (Research, Society and Development, 2022)
Introduction: The consequences of incorrect disposal of medicines are not few, they can be perceived not only in the contamination of soils, groundwater, rivers and oceans, but also in the alteration of some forms of life. Objective: The objective of this article is to carry out a bibliographic review on the issue of medication disposal in Brazil, reporting actions and mechanisms that may serve to reduce the negative impact of disposal. Methodology: The work was based on research of articles published in the period from 2012 to 2022, carried out through the survey of articles in the following databases: Scielo (Scientific Electronic Library Online), PubMed, and Lilacs, which following the inclusion criteria and exclusion, resulted in 20 included articles. Being based on a literature review, according to Cunha, Cunha & Alves, (2014). The following descriptors were used: Disposal of medication, disposal of medication in Brazil, incorrect disposal of medication. Conclusion: The correct disposal of medicines must take place at collection points throughout the city. The purpose of these products must be incineration. For this, the population needs to find the places where there are collection points to leave their expired or unused medicines at these points. The National Solid Waste Policy (PNRS) – Law No. 12,305/10 – establishes reverse logistics as the correct disposal of medicines. That is, when you find an expired medication at home, you must take it back to pharmacies or drugstores, which collect it and send it to the destination for proper decontamination and incineration.